Modification of MRI pattern of high‐grade glioma pseudoprogression in regorafenib therapy. Issue 3 (24th June 2021) - Mansour, Mariam; Vitale, Valerio; Lombardi, Giuseppe; Riva, Giulio; Pancheri, Francesca; Zanusso, Mariano
Abstract: Pseudoprogression (PP) is a diagnostic dilemma in the follow‐up of brain high grade gliomas (HGG), and the introduction of new therapies has further complicated its identification in Magnetic Resonance Imaging (MRI). We report a case of pseudoprogression after intraoperative radiotherapy (ioRT) and Regorafenib therapy in a patient with anaplastic astrocytoma recurrence. A 65‐year‐old man, treated in August 2017 for a right frontal anaplastic astrocytoma, with surgical resection and following radiotherapy and Temozolomide, in October 2019 was again treated for peri‐surgical bed recurrence with resection and ioRT followed by Regorafenib therapy, interrupted in February 2020, after the onset of adverse reactions. MRI examination showed a large irregular alteration posterior to the surgical bed, T2 weighted hypointense featuring strong diffusion restriction (low ADC values), with an irregular contrast‐enhancement (CE) pattern, and surrounded by a vast vasogenic oedema; Dynamic Susceptibility Contrast (DSC) perfusion imaging (PWI) showed no increase of relative cerebral blood volume (rCBV). Particularly, lesion appeared markedly hypointense and dusty‐like on susceptibility weighted images (SWI) probably due to a constant hemorrhagic diapedesis promoted by Regorafenib. Therefore, pseudoprogression was suspected. Follow‐up MRI exams showed gradual reduction of SWI and CE abnormalities, but a persistent DWI restriction. Unfortunately, the last MRI control showed a secondary cerebellar localisation of the disease. New therapies are changing MRI pattern in HGG imaging and this case underlines how a multimodality approach is increasingly necessary. In particular, when using anti‐VEGF drugs, SWI can have a crucial role in identifying therapy‐related haemorrhagic changes.